2023
DOI: 10.3389/fpubh.2023.1114248
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal analysis of pulmonary tuberculosis among students in the Zhejiang Province of China from 2007–2020

Abstract: BackgroundPulmonary tuberculosis (PTB) is a serious chronic communicable disease that causes a significant disease burden in China; however, few studies have described its spatial epidemiological features in students.MethodsData of all notified PTB cases from 2007 to 2020 in the student population were collected in the Zhejiang Province, China using the available TB Management Information System. Analyses including time trend, spatial autocorrelation, and spatial–temporal analysis were performed to identify te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…We also found that the symptoms of pulmonary tuberculosis among students in suburb district were mild; the positive rate of pathogens was low, and it was difficult to detect and diagnose compared to the general population, with strong concealment. It is necessary to strengthen students' active physical examination screening and molecular biological detection technology, which is consistent with the fact that students' tuberculosis patients are easily found in Wuhan every year during graduation, admission, and annual physical examination and similar to many research results (19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 55%
“…We also found that the symptoms of pulmonary tuberculosis among students in suburb district were mild; the positive rate of pathogens was low, and it was difficult to detect and diagnose compared to the general population, with strong concealment. It is necessary to strengthen students' active physical examination screening and molecular biological detection technology, which is consistent with the fact that students' tuberculosis patients are easily found in Wuhan every year during graduation, admission, and annual physical examination and similar to many research results (19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 55%
“…Conversely, other occupational segments depict a downward trajectory, indicative of enhanced health protection and preventive measures within those sectors.Notably, students rank third among all occupations, comprising 4.33% of cases, potentially re ecting RR-PTB transmission within campus settings. Strengthening health education and preventive measures within the student populace is warranted [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The overall trend is a gradual decrease from coastal cities to inland cities. High-quality medical and health resources are highly concentrated in the northern Zhejiang plain [40], especially in Hangzhou. There is a relative gap in the management level of hospitals in the southwestern region, so there is also a gap in the efficiency and thoroughness of process simplification linked to it.…”
Section: Regional Heterogeneity Of Wise Medical Constructionmentioning
confidence: 99%